Treatment effect of mTOR-inhibition on tissue composition of renal angiomyolipomas in tuberous sclerosis complex (TSC) - Brakemeier, Susanne; Vogt, Lars; Adams, Lisa; Zukunft, Bianca; Diederichs, Gerd; Hamm, Bernd; Budde, Klemens; Makowski, Marcus R. (PLoS ONE, 2017)
Purpose Tuberous sclerosis complex (TSC)-associated renal angiomyolipoma (AML) have a high lifetime risk of acute bleeding. MTOR-inhibitors are a promising novel treatment for TSCAML, however adequate response to therapy can be difficult to assess. Early changes in MRI signal may serve as a novel early indicator for a satisfactory response to mTOR-inhibitor therapy of AML. Materials and methods Thirty-eight patients with the definite diagnosis of tuberous sclerosis receiving everolimus therapy and n = 19 patients without specific therapy were included. 1.5 Tesla MRI was performed including sequences with a selective fat suppression. Patients were investigated prior to the initiation of therapy (baseline) and after <3 months (n = 21 patients), 3 to 6 months (n = 32) and 18 to 24 months (n = 28). Signal and size changes of renal AMLs were assessed at all different timepoints. Signal-to-noise-ratio (SNR), contrast-to-noise-ratio (CNR) and size of angiomyolipomas were evaluated. Results Signal changes in 273 AMLs were evaluated. A significant and strong decrease of the CNR of AMLs following the initiation of therapy was measured in the fat-suppressed MR sequence at all time points, compared to the baseline: From 7.41±6.98 to 3.84±6.25 (p-0.05p = 0.002), 3.36±6.93 (p<0.0001), and 2.50±6.68 (p<0.0001) after less than 3 months, 3±6 months or 18±24 months of everolimus treatment, respectively. Also, a significant, however less pronounced, reduction of angiomyolipoma size in the different groups was measured (from baseline 2022.2-2657.7 mm2 to 1854.4±1670.9 mm2 (p = 0.009), 1875.5-3190.1 mm2 (p<0.001), and 1365.8 ± 1628.8 mm2 (p<0.0001) after less than 3 months, 3±6 months or 18±24 months of everolimus treatment, respectively). No significant changes in CNR (p>0.05) and size (p>0.05) were measured in the control group. Conclusion mTOR inhibitor therapy in TSC patients results in an early and pronounced fatty transformation of AMLs on MRI. Fatty transformation could represent a novel early indicator of response to therapy in this patient collective.
CRIS-Team Scopus Importer:2023-03-08